2010
DOI: 10.1016/j.jvir.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Competing Imaging Measures of Response of Hepatocellular Carcinoma to Yttrium-90 Radioembolization

Abstract: Purpose There are currently at least 6 major competing criteria that are used to determine response to 90Y and other liver-directed therapies including: a) RECIST, b) WHO, c) volumetric, d) 2D EASL, e) 3D EASL, f) functional diffusion weighted (DW) MR imaging. Our purpose was to evaluate the agreement between these competing tumor response classification schemes based on quantitative measurements of tumor size, necrosis, and changes in water mobility. Materials/Methods In this retrospective study, 20 HCC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Such responses appear as arterially nonenhanced areas within treated lesions at dynamic CT or MR imaging ( 2 ). Researchers in recent studies have reported that the EASL criteria provide a signifi cant anatomic response and are useful prognosticators of clinical outcomes in HCC patients following chemoembolization or yttrium 90 radioembolization ( 11,18 ). With the EASL guidelines, a bidimensional method is used to estimate tumor load, on the basis of WHO size criteria.…”
Section: Vascular and Interventional Radiology: Response Criteria In mentioning
confidence: 99%
“…Such responses appear as arterially nonenhanced areas within treated lesions at dynamic CT or MR imaging ( 2 ). Researchers in recent studies have reported that the EASL criteria provide a signifi cant anatomic response and are useful prognosticators of clinical outcomes in HCC patients following chemoembolization or yttrium 90 radioembolization ( 11,18 ). With the EASL guidelines, a bidimensional method is used to estimate tumor load, on the basis of WHO size criteria.…”
Section: Vascular and Interventional Radiology: Response Criteria In mentioning
confidence: 99%
“…Overall response according to the Response Evaluation Criteria in Solid Tumors (version 1.1), the criteria of the World Health Organization, and the 2-dimensional criteria of the European Association for the Study of the Liver were used to evaluate 90 Y radioembolization as a part of comprehensive multimodality therapy for inoperable HCC, without regard to planning target volumes (28,30).…”
Section: Terms and Definitionsmentioning
confidence: 99%
“…Volumetric assessment of tumor anatomy and function by using diffusionweighted MR imaging and enhancement after contrast material administration has been successfully applied in the liver (22,23). Specifically, an increase in apparent diffusion coefficient (ADC) obtained from diffusion-weighted imaging after therapy has been shown to be associated with tissue edema, fibrosis, necrosis, and apoptosis (11,(24)(25)(26)(27). A decrease in contrast enhancement after intraarterial therapy is indicative of disruption of tumor blood supply and has increased substantially.…”
Section: Gastrointestinal Imaging: Unresectable Hepatocellular Carcinmentioning
confidence: 99%